Natures Echo Biomorphic Motifs in Orang Ulu Traditional Crafts - Marzie, Hatef Jalil; Qistina Donna, Lee Abdullah; Noorhaslina, Senin; Natasha, Rusdy Wong; Loh, Ngiik Hoon (UNIMAS PUBLISHER, 2025)
This book, Biomorphic Motifs in Orang Ulu Traditional Crafts, celebrates the intricate artistry and cultural significance of the Orang Ulu people's traditional designs, showcasing their profound connection to nature and heritage. It explores the evolution of biomorphic motifs, patterns inspired by organic forms, and their diverse applications, from ceremonial attire to modern adaptations. The book is richly illustrated, capturing the essence of Orang Ulu craftsmanship through historical artefacts, traditional textiles, and contemporary creations.